The Outcomes of Re-Exploration for Bleeding Following Coronary Artery Bypass Grafting (CABG) - Shazia Nazir, Humaira Batool, Syeda Tasneem Kausar, Rubina Jabeen, (Pakistan Journal of Medical & Health Sciences, 2022)
Objectives: The mainobjective of study was to explore the effect of re-exploration after coronary artery bypass (CABG). Material and Methods: This was descriptive cross sectional study conducted at cardiac surgery department during the period of 1st January to 30thJune, 2017. A pre design questionnaire was used to collect data on outcomes of all re-explored cases for post-operative bleeding that underwent CABG surgery. The data was analyzed by SPSS 20. Statistical test like chi- square test was applied to obtain the required results. Results: Findings of current study showed that the average age of patient was 38.2±4.2 years (age range 21-50 years). The male and female participants were 38(66%) and 20(34%), Low output syndrome 9(16%), IABP Support 5(9%), Arrhythmias 11(19%), Post-operative lung dysfunction 6(10%) and 3(9%) Stroke. Conclusion: Delay in re-exploration and massive amount of allergenic blood products are associate with a worse clinical outcome and an increase in mortality.